Catalytic Enantioselective Approaches to the oxa-Pictet–Spengler Cyclization and Other 3,6-Dihydropyran-Forming Reactions - Zhu, Zhengbo; Adili, Alafate; Zhao, Chenfei; Seidel, Daniel (SynOpen, 2019)
This Short Review provides an analysis of the state-of-the-art in catalytic enantioselective oxa-Pictet–Spengler cyclizations. Also discussed are other catalytic reactions providing access to enantioenriched isochromans and tetrahydropyrano[3,4-b]indoles. Context is provided and remaining challenges are highlighted.
Keywords: oxa-Pictet–Spengler cyclization; isochromans; tetrahydropyrano[3,4-b]indoles; oxocarbenium ions; asymmetric catalysis; ion pairing